Estudo da resistência à corrosão de ligas de alumínio com grãos ultrafinos obtidos por deformação plástica severa através do processo ECAP - Quartiermeister, Marcelo Valerio (Universidade Federal de São Carlos, 2017)
The present work evaluated the effect of severe plastic deformation and ultrafine grains, obtained through the ECAP (equal-channel angular pressing) process, in the corrosion resistance of AA1050 aluminum alloy. The microstructural changes were observed through optical microscopy and scanning electron microscope (SEM) with energy dispersive x-ray (EDX). Mechanical properties were evaluated with tensile test and Vickers microhardness. The corrosion resistance was evaluated through potentiodynamic polarization tests in 0,1M sodium sulfate (Na2SO4) and 300 ppm of NaCl solution. Additionally, immersion test was performed in NaCl and H2O2 solution with the objective of evaluating intergranular corrosion. Optical microscopy analysis revealed a decrease in grain size with the increase number of ECAP passes. SEM analysis shows that ECAP process brakes down course precipitates and disperses them throughout the material. EDX evaluation indicates that these precipitates are composed of Al, Si, Fe, Cu and Ti. Tensile test showed an increase in the yield strength of the material with increase ECAP passes. The total elongation is smaller compared to the non processed material, but there is an increase with each ECAP pass. It was possible to observe that ECAP decreases the uniform elongation. Vickers microhardness values increase until forth ECAP pass, than stabilizes. Potentiodynamic polarization analysis showed, for this experiment, an improvement in the average pitting potential values for the materials processed in ECAP. However, large variations of the data doesn´t allow us to conclude that statistically there is an improvement. SEM/EDX analysis after potentiodynamic polarization test showed that pits begin in the Al precipitates. In this case many other impurities were observed in the precipitates. Immersion test showed no signs of intergranular corrosion in any condition analyzed.
Corrosion resistance study of ultrafine – grained aluminum alloy obtained through severe plastic deformation in ECAP process
Keywords: Alumínio AA1050; Deformação plástica severa; Extrusão em canal angular; Corrosão por pite; Polarização potenciodinâmica; Aluminum AA1050; Severe plastic deformation; Equal-channel angular pressing; Pitting corrosion; Potentiodynamic polarization; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA